(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article deals with the current problems of discipline «Professionally – oriented Kazakh language» and about the innovations of reference disciplines at Law Faculty in Russian-speaking audience. In contrast to the humanities such as psychology, philosophy, political science, cultural studies and the history, this subject has explicitly expressed the practical and educational orientation and forms language skills and the ability of future specialists to provide both adequate perception of the texts in their specialty. Today’s situation is expecting mature reading and listening that promotes and is particularly important for producing their own speech and oral work in accordance with the situation in the official language of communication. Communication language of the criminal world is differ from others with its word derivatives and slang, and it requires the same consideration of modern translation from Russian into Kazakh language without sacrificing semantic link in the linguistic aspect and at the same time to give the notion that such words is also available in the Kazakh language.